Microwave Pioneers: Mau-Chung Frank Chang, “The Power of Connections” - Peter H. Siegel (IEEE Journal of Microwaves)
We are pleased to pick up this continuing series on individuals within our community who have made significant impacts in the field of microwaves, and to the world, over the course of their careers. This issue's Microwave Pioneer article is about Mau-Chung Frank Chang, who perhaps more than anyone else, is responsible for the widespread commercial use of the heterojunction bipolar transistor (HBT). Professor Chang is also an example of a researcher who very successfully crossed over from industry to academia and from research to management and back, having spent time in charge of a large team of commercial semiconductor fabrication engineers and as President of a major academic university. Throughout his very varied career, he always emphasized two things: the first he attributes to his mother's teaching - the great power of connecting individuals together to solve problems rather than trying to lead them to a solution, and the second – which is all his own – the fortitude to take on and stick with challenges that seemed daunting to others. We think you will benefit from hearing Frank's story and in getting to know him on a more personal level.